Fe3O4/TiO2 core/shell magnetic nanoparticle-based photokilling of pathogenic bacteria. (December 2010) - Chen, Wei-Jen; Chen, Yu-Chie
Aims: We demonstrate a photokilling approach for pathogenic bacteria using magnetic nanoparticles as photokilling nanoprobes.Materials & methods: The nanoprobes are composed of iron oxide/titania (Fe3 O4 /TiO2 ) core/shell magnetic nanoparticles. The titanium layer on the magnetic nanoprobes plays two roles: as a photokilling agent and as an affinity substrate for pathogenic bacteria. The magnetic property of the nanoprobes allows the resultant nanoprobe–target species conjugates to be readily aggregated at a small spot under external magnetic field for conducting photokilling treatment. Therefore, damage to nontarget cells can be reduced.Results: The results show that Fe3 O4 /TiO2 core/shell magnetic nanoparticles do not only have the capacity to target pathogenic bacteria, including Gram-negative, Gram-positive and antibiotic-resistant bacteria, but they can also be used to effectively inhibit the cell growth of the bacteria (>99.9%) targeted by the magnetic nanoparticles under irradiation of a low-power UV lamp (λmax ∼306 nm, 0.412 mW/cm 2 ) within 15 min.Conclusion: The potential application of this approach is in the treatment of cutaneous bacterial infections.